Patient willingness to receive full‐body skin exams based on the sex and/or gender and training level of provider: a survey study. (3rd July 2022) - Perche, Patrick O.; Ranpariya, Varun K.; Swali, Ritu N.; Clarey, Dillon D.; Wysong, Ashley; Feldman, Steven R.
Abstract: Full‐body skin examinations (FBSEs) involve examination of the patient's skin from head to toe, and may be uncomfortable for some patients. While many patients prefer same‐sex providers for pelvic, genital and rectal exams, desire for same‐sex providers for FBSEs is not well characterized. This may be further magnified when FBSE is performed by medical trainees. We surveyed 566 subjects using Amazon Mechanical Turk (AMT), an online crowdsourcing platform, to assess the public's willingness to receive FBSEs based on the sex and/or gender and the level of training of the healthcare provider (HCP). The overall willingness by all respondents to undergo FBSE performed by a dermatologist, dermatology resident and medical student was 84.3%, 77.5% and 65.7%, respectively, if the HCP was the same sex/gender, compared with 60.6%, 54.8% and 45.7% if the HCP was a different sex/gender ( P < 0.001). In our cohort, unwillingness for FBSEs was greater if the patient was female, if the HCP was a different gender/sex from the patient and if the HCP was a medical student.